2022
DOI: 10.3389/fphys.2022.949607
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Odorant-Binding Proteins and Chemosensory Proteins in the Bean bug Riptortus pedestris

Abstract: Insects have sensitive olfactory systems to interact with environment and respond to the change in host plant conditions. Key genes in the system can be potential targets for developing new and efficient pest behaviour control methods. Riptortus pedestris is an important soybean pest in East Asia and has caused serious damage to the soybean plants in Huang-Huai-Hai region of China. However, the current treatment of pests is dominated by chemical insecticides and lacks efficient sustainable prevention and contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…The genomic and transcriptomic data of R. pedestris have been published to study its development, chemosensory genes, and insecticide resistance [20,[23][24][25]41,42]. Previous qRT-PCR studies on R. pedestris commonly employed universal reference genes for insect species [23][24][25][26]. Nevertheless, the use of inappropriate ones may result in misinterpretation of data.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The genomic and transcriptomic data of R. pedestris have been published to study its development, chemosensory genes, and insecticide resistance [20,[23][24][25]41,42]. Previous qRT-PCR studies on R. pedestris commonly employed universal reference genes for insect species [23][24][25][26]. Nevertheless, the use of inappropriate ones may result in misinterpretation of data.…”
Section: Discussionmentioning
confidence: 99%
“…We selected odorant-binding protein 37 (RpedOBP37) [25] and cytochrome P450 6a2 (RpedCYP6) [26] for the validation of the most stable reference genes (EF1 and Actin) and a variable one (SDHA). The forward primer and reverse sequences for Rpe-dOBP37 were 5 -ATGGGAGCGATTTCTGAT-3 and 5 -ATAGCGGTTTCACATCCA-3 , while the primer pairs for RpedCYP6 were 5 -TACGGTCGAGGTTATCTG-3 and 5 -GGGCTGGTTATCCTTACT-3 .…”
Section: Validation Of the Candidate Reference Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, the information available for CSPs, also known as sensory appendage proteins (SAPs), indicated that these small soluble proteins involved in diverse activities and endowed with heterogeneous functions, such as serving as carrier proteins for binding and delivering hydrophobic compounds in chemosensory process ( Robertson et al 1999 , Pelosi et al 2006 , 2018 , Fu et al 2020 ). Studies on the molecular structures suggested CSPs are constituted by 4 conserved cysteines, which arrangement mode shown as Cys 1 -X6-Cys 2 -X18-Cys 3 -X2-Cys 4 , and linked by disulfide bridges between 2 adjacent cysteine residues that resulted in the formation of 2 small loops ( Angeli et al 1999 , Zhu et al 2016 , Pelosi et al 2018 , Zeng et al 2019 , Li et al 2022 ). Research on the binding abilities showed that CSPs have good affinities with many chemicals, which later was identified that the 2 formed disulfide bridges do not place constraints on the scaffolding of the CSPs, so the proteins can enlarge their binding cavities and adapt to binding different components ( Yi et al 2014 , Pelosi et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%